2006
DOI: 10.1039/b609282a
|View full text |Cite
|
Sign up to set email alerts
|

Solution structures of thiopeptide antibiotics

Abstract: A detailed NMR study of the thiopeptide amythiamicin D establishes its solution conformation and the presence of a single intramolecular hydrogen bond involving NH13 and O28, and also provides the first evidence for self-association of thiopeptides in solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
(25 reference statements)
1
9
0
3
Order By: Relevance
“…These residues are in proximity to the nitrogen atoms of the adjacent thiazol(in)e ring, which could explain their high protection against exchange. In line with earlier reports, [12] we found atypical properties for the dehydroamino acids, which likely reflects their enamine character.…”
Section: Dedicated To Professor Peter B Dervansupporting
confidence: 91%
See 1 more Smart Citation
“…These residues are in proximity to the nitrogen atoms of the adjacent thiazol(in)e ring, which could explain their high protection against exchange. In line with earlier reports, [12] we found atypical properties for the dehydroamino acids, which likely reflects their enamine character.…”
Section: Dedicated To Professor Peter B Dervansupporting
confidence: 91%
“…While 1 and related thiopeptides have been structurally characterized by NMR spectroscopy, [11] investigations on the conformation with current methods are scarce. [12] Here, we report solution-phase structures of 1 and three derivatives, and correlate their molecular interactions at the GAR of the 70S ribosome with their bioactivity.…”
Section: Dedicated To Professor Peter B Dervanmentioning
confidence: 97%
“…Während 1 und verwandte Thiopeptide zur Strukturaufklärung früh durch NMR-Spektroskopie charakterisiert wurden, [11] sind Studien zur Konformation mit heute üblichen Methoden selten. [12] Wir berichten hier über die Strukturen von 1 sowie von drei Derivaten in Lösung und korrelieren ihre molekulare Wechselwirkung an der GAR des 70S-Ribosoms mit ihrer biologischen Aktivität.…”
Section: Professor Peter B Dervan Gewidmetunclassified
“…Diese Reste liegen sehr nahe bei den Stickstoffatomen der benachbarten Thiazol(in)ringe, was ihre starke Abschirmung gegen chemischen Austausch erklären könnte. Über-einstimmend mit früheren Berichten [12] stellten wir untypische Eigenschaften der Dehydroaminosäuren fest, was wahrscheinlich an ihrem Enamincharakter liegt.…”
Section: Professor Peter B Dervan Gewidmetunclassified
“…Although our synthetic material appeared to be absolutely identical to the natural product, one signal in the 1 H NMR spectrum, assigned to NH29, showed significant concentration dependence. This prompted a more detailed NMR study [105] that not only revealed the presence of a single transannular hydrogen bond involving NH13 and O28, but also evidence for selfassociation of the thiopeptide in solution. These features are perhaps not surprising: with molecular weights of over 1000 Da, and arrays of rings linked by peptide bonds, the thiopeptides can be regarded as a microcosm of the protein world.…”
Section: Amythiamicin Dmentioning
confidence: 97%